2020
DOI: 10.3766/jaaa.18065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Remote Microphone System with Tri-Microphone Beamformer

Abstract: Children with hearing loss often experience difficulty understanding speech in noisy and reverberant classrooms. Traditional remote microphone use, in which the teacher wears a remote microphone that captures her speech and wirelessly delivers it to radio receivers coupled to a child’s hearing aids, is often ineffective for small-group listening and learning activities. A potential solution is to place a remote microphone in the middle of the desk used for small-group learning situations to capture the speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Similar improvements with adaptive multiple-microphone beamforming technology were reported for hearing aid users relative to a hearing-aid alone. 13 Across SNRs, the use of the remote microphone with multitalker network improved speech recognition in noise by an impressive average of 28 to 49 percentage points relative to the CI alone. The greater improvement in speech recognition in noise obtained with the multi-talker network relative to the adaptive multiple-microphone beamformer is likely due to differences in microphone positioning and technology features.…”
Section: Discussion Speech Recognition In Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Similar improvements with adaptive multiple-microphone beamforming technology were reported for hearing aid users relative to a hearing-aid alone. 13 Across SNRs, the use of the remote microphone with multitalker network improved speech recognition in noise by an impressive average of 28 to 49 percentage points relative to the CI alone. The greater improvement in speech recognition in noise obtained with the multi-talker network relative to the adaptive multiple-microphone beamformer is likely due to differences in microphone positioning and technology features.…”
Section: Discussion Speech Recognition In Noisementioning
confidence: 99%
“…Specifically, a remote microphone with an adaptive multiple-microphone beamformer may be placed in the center of the small group, and the beam (i.e., polar lobe) may be automatically steered toward the direction with the best SNR to allow wireless delivery to the CI processor. Wolfe and colleagues 13 report that remote microphone systems with adaptive multiple-microphone beamforming significantly improved speech recognition in small group settings by 24 percentage points in a group of 15 children using hearing aids relative to their aids alone. However, to date, no studies have explored the potential benefits of adaptive multiple-microphone beamforming for CI recipients.…”
mentioning
confidence: 99%
“…Prior research has shown that, on average, the use of RM improves children's speech perception in complex listening environments, and the insufficient benefit for some children has not been explored in-depth in many studies. Wolfe, Duke [ 1 ] explored modern RM with adaptive functions for solving the ineffectiveness of earlier technologies for small-group listening and interactive lessons [ 1 ]. Modern types of devices, through different functions and modes, focus on the special needs of children in different listening situations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of primary compensatory devices (hearing aids/cochlear implants), children who are hard of hearing (HoH) are disadvantaged compared to their peers. These disadvantages include speech recognition under noisy conditions or understanding speech at a greater distance [ 1 , 2 , 3 ]. This do not necessarily mean that the child cannot hear or understand, but they usually find listening more difficult and have to exert more effort than their classmates with normal hearing [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] HAs alone may not be able to overcome the adverse effects of noise, distance, and reverberation in classrooms since amplification is applied to whatever combination of signals reach the microphone. [29][30][31] However, children who are hard of hearing and who have greater aided audibility have been shown to demonstrate better speech understanding in a variety of acoustic environments than children with poorer audibility. 4,[32][33][34][35] It is possible that better-aided audibility with HAs could correspond to better speech understanding when those HAs are used with RM systems than when HAs with poorer aided audibility are used with RM systems.…”
mentioning
confidence: 99%